Occurrence of Canine Babesiosis in Dogs of Jaipur: Canine Babesiosis - Gurjar, Vikram Singh; Singh, Dr. Rashmi; Jeph, Nirmal Kumar; Sharma, Sandeep Kumar; Sarswat, Chandra Shekhar; Choudhary, Akanksha; Devendra (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
In this study, 200 Babesiosis suspected dogs were included which was presented at PGIVER, Jaipur and Govt. veterinary polyclinic, Jaipur with the history of inappatance to anorexia, pyrexia, tick infestation, lethargy and signs of anemia during study period and out of these 200 suspected cases, 16 dogs were confirmed for babesiosis by conventional microscopic technique and revealed 8 percent (16/200) prevalence of the infected cases. The highest prevalence was found in age group of 2-5 years (50%), and among the various breeds affected, Labrador retriever constituted the maximum of 8/16 (50%) cases in total and Sex wise prevalence revealed that females were more susceptible as compared to males.